2020
DOI: 10.36348/sjef.2020.v04i07.006
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fintech on Development of Islamic Banking Sector in the Contemporary World

Abstract: Technologies of the future drive an important role in effective growth of Islamic banking sector by creating transformational waves fostering the emersion of "Fintech", which, compared to the traditional financial system, fulfills several advantages. Financial technologies appear to have a significant participation in the empowerment of individuals who lack access to financial services and consequently lead to immediate and continuing interest for individuals, the planet, and wealth. The rapid alteration of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Islamic banks are limited by higher costs connected with shariah advisors, specificities products and auditors. The levels of innovation in Islamic financial institutions are low because the evolution of Islamic finance is regarded as a recent activity (Al-Salem, 2009;Panjwani and Shili, 2020). When compared to conventional banks, Islamic banks appear to be slower to respond to the influence of FinTech (Ali et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Islamic banks are limited by higher costs connected with shariah advisors, specificities products and auditors. The levels of innovation in Islamic financial institutions are low because the evolution of Islamic finance is regarded as a recent activity (Al-Salem, 2009;Panjwani and Shili, 2020). When compared to conventional banks, Islamic banks appear to be slower to respond to the influence of FinTech (Ali et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Technologies play an important role in effective growth of Islamic banking industry by transformational waves, which can be compared to the traditional banking system. Due to innovations in financial technology, the quick changes in financial sector have been spread all over the world in banking sector and in Islamic banking sector in particular (Panjwani & Shili, 2020). The innovation in information technology has emerged to ease daily banking commercial transactions.…”
Section: Discussionmentioning
confidence: 99%
“…Yudaruddin (2022) explains that Islamic banks face higher costs associated with Sharia advisors and have lower levels of innovation compared to conventional banks. Panjwani and Shili (2020) also point out that the degree of innovation in Islamic financial entities is generally low. Furthermore, Ali et al (2019) have found that Islamic banks respond slower to the impact of FinTech when compared to conventional banks.…”
Section: Fintech and Banksmentioning
confidence: 96%